An analysis of the impact of Islamic microfinance among Asnaf - Redzuan, Nur Harena; Kassim, Salina; Rosman, Romzie; Muhammad Zuki, Mohd Faizuddin; Shaharuddin, Siti Saffa (2022)
Microfinance has been proven that it is an effective tool for poverty reduction and socioeconomic development. Yet, the impact of microfinance on the recipients is still questioned and varies from one institution to others. This research analyzes the impact of Islamic microfinance on asnaf. The study employs a qualitative research method by using primary data collection. The input for the study is obtained from the semi-structured interview with the representatives of State Islamic Religious Councils (SIRCs) and Islamic financial institutions. The originality of this study may contribute to the formation of a new body of knowledge and enrich the literature sources in the field of Islamic microfinance that will benefit both academicians and practitioners. This impact study on performance and measurement may significantly contribute toward the sustainable and socially impactful growth of the Islamic finance industry, especially in achieving the maqasid Shari-ah and Value Based Intermediation (VBI) goals.